Islam and Eco-Spirituality of the Merapi Society - Khoiriyah, Amri; Mujib, Abdul; Lubis, Sopian; Alamri, Mohammed Saeed A. (JURNAL INDO-ISLAMIKA, 2024)
This study aims to prove that environmental balance results from an equal dialogue between humans and nature in the divine frame. In addition, the study will analyze how Islamic spirituality is integrated into the spiritual ecology of the Merapi community, which involves elements of God, nature, and humans in the context of environmental balance. This research is qualitative, using a grounded research method. This research mainly uses an ecological approach that includes anthropological aspects. The main source is data on the ecological wisdom of the Merapi people. Secondary sources are books, journals, and manuscripts on themes relevant to the research discussion. Collecting data through interviews, observations, and documentation. The findings are that spiritual ecology, manifested in the Merapi people's ecological wisdom, has a relationship with environmental balance. In a review of the spiritual ecology of the Merapi community, it can be stated that the more dominant the spiritual aspect of humans is, the more straight their life behavior is, lurus, leres, and laras. Several aspects interact with each other in the spiritual ecology of the Merapi community: Islamic spirituality, ecology, and local wisdom.